Internalization of Religious Values through the Friday Infaq Program as a Character Education Strategy in Islamic Primary Schools - M. Luqmanul Hakim Habibie; Nursalamah (Journal of Contemporary Applied Islamic Philanthropy, 2025)
Purpose: This study aims to analyse the mechanism of internalizing religious values through the Friday Infaq program and its contribution to students’ character formation in Islamic primary schools (Madrasah Ibtidaiyah). Methodology: The research employed a descriptive qualitative approach, involving the principal, teachers, and students of MI Ma’arif 18 Trimurjo as research participants selected through purposive sampling. Data were collected through participatory observation, in-depth interviews, and document analysis, and subsequently analysed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. Data credibility was ensured through source and technique triangulation. Findings: The findings indicate that the Friday Infaq program functions as an effective strategy of religious habituation in instilling values of sincerity, responsibility, empathy, and social awareness among students from an early age. The internalization of these values occurs through teachers’ role modelling, institutionalized routines, and active parental involvement. Theoretically, this study reinforces the perspective of character education grounded in experiential learning within the context of Islamic philanthropy, while also extending previous studies that have predominantly focused on secondary education levels. This research highlights that simple philanthropic practices, when implemented consistently, can serve as sustainable instruments for character education at the primary education level.